Cell alignment modulated by surface nano-topography – Roles of cell-matrix and cell-cell interactions. (1st April 2022) - Coyle, Stephen; Doss, Bryant; Huo, Yucheng; Singh, Hemang Raj; Quinn, David; Jimmy Hsia, K.; LeDuc, Philip R.
Abstract: The propensity of cells to align in particular directions is relevant to a number of areas, including tissue engineering and biohybrid robotics. Cell alignment is modulated through various extracellular conditions including surface topographies, mechanical cues from cell-matrix interactions, and cell-cell interactions. Understanding of these conditions provides guidance for desirable cellular structure constructions. In this study, we examine the roles of surface topographies and cell-cell interactions in inducing cell alignment. We employed wavy surface topographies at the nanometer scale as a model extracellular environment for cell culture. The results show that, within a certain range of wavelengths and amplitudes of the surface topographies, cell alignment is dependent on cell confluency. This dependence on both topology and confluency suggests interplay between cell-cell and cell-matrix interactions in inducing cell alignment. Images of sparsely distributed and confluent cells also demonstrated clear differences in the structures of their focal adhesion complexes. To understand this effect, we introduced anti-N-cadherin to cell culture to inhibit cell-cell interactions. The results show that, when anti-N-cadherin was applied, cells on wavy surfaces required greater confluency to achieve the same alignment compared to that in the absence of anti-N-cadherin. The understanding of the cell alignment mechanisms will be important in numerous potential applications such as scaffold design, tissue repair, and development of biohybrid robotic systems. Statement of significance: Cell alignment plays a critical role in numerous biological functions. Advances in tissue engineering utilizes cell alignment to restore, maintain, or even replace different types of biological tissues. The clinical impact that tissue engineering has made is facilitated by advancements in the understanding of interactions between scaffolds, biological factors, and cells. This work further elucidates the role of cell-cell interactions in promoting the organization of biological tissues. Graphical abstract: Image, graphical abstract